A framework for using optical sensors in nanomeasuring machines over I++/DME - Sparrer, Erik; Machleidt, Torsten; Hausotte, Tino; Franke, Karl-Heinz; Manske, Eberhard (Measurement Science & Technology, 2012)
This paper discusses the problem of integrating optical sensors into CMMs. First the basic concept of optical sensors is briefly introduced as well as the targeted measurement implementation standard, I++DME, and the Optical Sensor Interface Standard, which is still seldom used but is gaining acceptance. A novel generic software framework is introduced which helps to simplify the use of optical sensors in CMMs. To demonstrate the feasibility of integrating an optical sensor into a CMM, the framework has been successfully implemented around a white light interferometer, in which the sensor system is mounted in an ultra-precision CMM. The actual process control and data analysis was done using a third-party metrology application, which does not normally support either ultra-precision CMMs or optical sensors.
Keywords: nanopositioning and nanomeasuring machine; NPMM; Inspection plus plus for Dimensional Measurement Equipment; I plus plus DME; Optical Sensor Interface Standard; OSIS; framework; white light interferometry